Mechanical mechanism of suture passer needle break in rotator cuff repair - Yang, Chunxi; Xie, Cheng; Liu, Hui; Hua, Zikai; An, Bingchen (Frontiers in Surgery, 2022)
Abstract Suture passer needle, as one of commonly used instrument in the arthroscopic rotator cuff repair, often breaks at the notch of the needle which originally was designed to facilitate suture with thread. Our study aimed to evaluate suture failure rate and stitch success rate between intact suture needle and broken needle and explore the mechanism of the needle breakage and achieving better future designs. Materials and Methods From 2017 to 2021, consecutive 437 shoulders (11 cases were bilateral) underwent arthroscopic repair for full-thickness rotator cuff tear at the authors’ institution. The broken of needles were recorded. Finite elements analysis and mechanical test was utilized to compare stress distribution，Puncture performance, and loaded Puncture performance between broken needle and intact needle. Results We identified 19 consecutive patients who had the incident that the needle tip of TruePassTM suture passer was broken in 437 shoulders surgery. Based on the finite element analysis of Abaqus, around the tip and the notch of the intact needle had a large stress concentration. The average puncture force required by intact needle tip and the broken tip is 61.78N and 78.23N respectively. While the intact tip with notch is easier to break than the broken tip. Conclusions The notch of the needle is a weak point in mechanics. The broken needle without notch, still has good tendon piercing and thread passing ability. And the notch of needle maybe is not necessary, the tip of needle should be modified.